2022
DOI: 10.1021/acs.joc.2c00059
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Promoted Intramolecular C–O Bond Formation via Csp3H Functionalization: A Straightforward Synthetic Route to Biorelevant Dihydrofuro[3,2-c]chromenone Derivatives

Abstract: A photochemical method for the synthesis of functionalized dihydrofuro­[3,2-c]­chromenones via intramolecular Csp3 –H cross-dehydrogenative oxygenation within a warfarin framework has been unearthed. Advantages of this protocol include abundant sunlight or low-energy visible light as the energy source, mild reaction conditions, and avoidance of metal catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 60 publications
(15 reference statements)
1
7
0
Order By: Relevance
“…On the basis of previous related reports ,,, and our experimental results presented above, a plausible reaction pathway is illustrated as shown in Scheme . Interaction of CBr 4 with DMF under irradiation generates a radical intermediate A and bromo radical.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…On the basis of previous related reports ,,, and our experimental results presented above, a plausible reaction pathway is illustrated as shown in Scheme . Interaction of CBr 4 with DMF under irradiation generates a radical intermediate A and bromo radical.…”
mentioning
confidence: 78%
“…Consequently, developing simple and efficient methods to construct structurally diverse substituted coumarins has attracted much attention, and a number of strategies have been well developed . In the past decade, visible-light-induced radical-involved cyclization reactions have been established as a viable approach for the synthesis of functionalized coumarins under mild conditions, which gained much populartity in organic synthesis . In this context, due to their easy preparation and susceptibility to radical addition, aryl alkynoates have been employed as well-known radical acceptors in a range of visible-light-induced cyclizations for the construction of diverse substituted coumarins …”
mentioning
confidence: 99%
“…Mandal et al in 2022 reported rose bengal catalysed direct carbon-hydrogen functionalization of warfarin analogsto produce dihydrofuro[3,2-c]chromenones based on intramolecular carbon-oxygen bond formation under visible light at ambient temperature (Scheme 25). [112] The various conditions of the reaction were screened with warfarin analog to study the usual circumstances for intramolecular sp 3 hybridized CÀ H cross-dehydrogenative oxygenation in visible light illumination. The reactions were conducted under blue LEDs as well as under direct sunlight with the optimized set of reaction conditions.…”
Section: Synthesis Of Functionalized Dihydrofuro[32-c] Chromenone Der...mentioning
confidence: 99%
“…11 Despite these, the development of an efficient methodology for the synthesis of 2,3-dihydro-4H-furo [3,2-c] accessible reagents under environment-friendly conditions is highly desirable from the viewpoint of green chemistry. In 2018, Yang et al reported that α-C(sp 3 )-H functionalization of aryl ketones could be carried out through visible-light photocatalysis (Scheme 1). 12 Inspired by these works, we envisaged that the 2,3-dihydro-4H-furo [3,2-c]chromen-4-ones could be easily synthesized from the Michael adduct of 4-hydroxycoumarin and chalcones under visible light irradiation.…”
mentioning
confidence: 99%
“…Then, the effect of different additives on this reaction was checked and it was observed that TBAI (1 equiv.) was the best additive for this transformation among TBAI, KI, NaI, NaBr and NaCl (Table 1, entries [3][4][5][6][7]. Lowering the amount of TBAI (0.5 equiv.)…”
mentioning
confidence: 99%